Monocyte subpopulations of blood and bone marrow in patients with chronic heart failure - M. V. Vins; S. P. Chumakova; O. I. Urazova; D. A. Azarova; V. M. Shipulin; A. S. Pryakhin; S. E. Barmina; M. D. Werner; V. V. Novitskiy (Бюллетень сибирской медицины, 2018)
The aim of the investigation was to evaluate the ratio of classical (CD14++CD16-), intermediate (CD14++CD16+), nonclassical (CD14+CD16+) and transient (CD14+CD16–) monocytes in the blood and bone marrow in patients with chronic heart failure (CHF) against ischemic cardiomyopathy (ICMP).Materials and methods. 17 patients with ICMP and 14 practically healthy donors were observed. The material of the study was venous blood (in patients and healthy donors) and red bone marrow (in patients). In the materials the relative content of different monocytes subpopulations was determined by flow cytometry. The obtained results were analyzed by statistical methods.Results. It is shown that in the blood of patients the proportion of monocytes with the phenotype CD14++CD16- is 57.77 [of 46.35; 79.76]%, CD14++CD16+ – 25.06 [4.96; 42.31]%, CD14+CD16+ 5.05 [4.08; 6.58]% and CD14+CD16- – 6.03 [3.58; 10.89]%; in the bone marrow – 43.44 [40.54; 44.68]%, 0.16 [0; 1.07]%, 0,54 [0.35; 1.07]% and 54,32 [52.83; 56.08]%, respectively, which is different from the content of the data cells subpopulations in the blood (p < 0.05). At the same time, the content of non-classical monocytes in the patients’ blood is 2 times lower than in healthy donors, and the number of other cells varies within the norm.Conclusion. The differentiation of monocytes into 4 subpopulations in patients with CHF occurs directly in the bloodstream, since mainly the classical and transitional monocyte fractions with the prevalence of the latter are present in the bone marrow. Deficiency of non-classical monocytes of blood in CHF is probably associated with a disruption of their extramedullary differentiation.